Potent antitumour activity of interleukin-2-Fc fusion proteins requires Fc-mediated depletion of regulatory T-cells - Rodrigo Vazquez-Lombardi (Nature Portfolio, 2017)
Interleukin-2 (IL-2) is a T-cell proliferating factor used for cancer immunotherapy. Here, the authors develop a long-lived variant of IL-2 that, mutated in its binding domain, drives a much more potent tumour regression by depleting CD25+ CD4+regulatory T-cells via targeting them for phagocytosis.